2020
DOI: 10.1186/s12864-020-06882-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of the uterus of hens laying eggs differing in cuticle deposition

Abstract: Background: Avian eggs have a proteinaceous cuticle. The quantity of cuticle varies and the deposition of a good cuticle in the uterus (Shell-gland) prevents transmission of bacteria to the egg contents. Results: To understand cuticle deposition, uterus transcriptomes were compared between hens with i) naturally good and poor cuticle and, ii) where manipulation of the hypothalamo-pituitary-gonadal-oviduct axis produced eggs with or without cuticle. The highest expressed genes encoded eggshell matrix and cuticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 56 publications
2
14
0
Order By: Relevance
“…The current study found that regardless of dietary Se treatments, mRNA expression of OCX-32 and OCX-36 was up-regulated in the shell gland than in magnum tissue. Poyatos et al [ 57 ] and Yin et al [ 44 ] identified highly expressed OCX-32 precursors in the shell gland with egg, which is consistent with our findings. Similarly, Yin et al [ 60 ] found that the OCX-32 gene was expressed higher in the distal oviduct (isthmus and shell gland) than in the proximal oviduct (magnum and shell gland), suggesting that it is secreted by the glandular epithelium of the shell gland [ 61 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current study found that regardless of dietary Se treatments, mRNA expression of OCX-32 and OCX-36 was up-regulated in the shell gland than in magnum tissue. Poyatos et al [ 57 ] and Yin et al [ 44 ] identified highly expressed OCX-32 precursors in the shell gland with egg, which is consistent with our findings. Similarly, Yin et al [ 60 ] found that the OCX-32 gene was expressed higher in the distal oviduct (isthmus and shell gland) than in the proximal oviduct (magnum and shell gland), suggesting that it is secreted by the glandular epithelium of the shell gland [ 61 ].…”
Section: Discussionsupporting
confidence: 93%
“…Regardless of the treatment groups, the results showed higher mRNA expression of OC-17 and OC-116 in the shell tissue than in magnum. This was confirmed by published data [ 19 , 44 , 46 , 57 ], who found higher OC-116 genes mRNA expression in the shell gland tissue. Furthermore, there has been an interaction between organic matrix and inorganic minerals in chicken uterine fluid, resulting in tough and calcification of eggshell [ 19 ].…”
Section: Discussionsupporting
confidence: 89%
“…Eggshell calcification in the uterus of laying hens involves multiple cellular and molecular processes, including calcium carbonate secretion, transport and biological mineralization ( Sah et al, 2018 ; Khan et al, 2019 ). It has been reported that circadian clock is a major component and significantly controls cuticle deposition in the uterus of laying hens ( Poyatos et al, 2020 ). We found functional clocks in the chicken infundibulum and uterus ( Zhang et al, 2016 ; Zhang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent finding reported that endogenous clock is a major component and significantly controls cuticle deposition in the uterus of laying hens ( Poyatos et al, 2020 ). To clearly understand the control mechanisms of uterine clock exerted on CCGs regarding the phases in a day, a systemic understanding of the dynamic transcriptional regulations of the circadian clock is necessary.…”
Section: Introductionmentioning
confidence: 99%